Analysis of Takhrij Hadith in the DSN-MUI Fatwa on Halal Tourism: A Critical Study of the Sanad and Matan - Fahmi, Muhammad; Ulfianti; Muttaqin, Mohammad Izdiyan; Hannase, Mulawarman (Institut Agama Islam Negeri (IAIN) Curup, 2025)
DSN-MUI Fatwa No. 106/DSN-MUI/X/2016 regarding halal tourism is a significant reference in Indonesia. This research analyzes the authenticity of the hadiths within this fatwa using a qualitative method with a takhrij al-hadith approach, focusing on the quality of the sanad (chain of narrators) and matan (text). The primary data sources are the DSN-MUI fatwa, hadith collections, and narrator biographies (rijal al-hadith) such as Tahzib al-Tahzib and Tahzib al-Kamal. Findings indicate that two hadiths narrated by Imam Ahmad and Imam al-Baihaqi are classified as dhaif (weak) but may be used for fadha'il al-a'mal (virtues of deeds) if their weaknesses are not severe. Conversely, a hadith narrated by Abd al-Razzaq is deemed sahih (authentic). This study contributes by performing takhrij from Mashadir al-Asliyah (primary sources) on the hadiths of the halal tourism fatwa, an underexplored area.